Advances in physics of Rydberg atoms and molecules - Oks, E. A. (Evgeniæi Aleksandrovich) (IOP (Series). Release 21., 2021)
This book covers recent analytical advances in the study of Rydberg atoms and molecules. The book presents classical descriptions of electron trajectories in Rydberg atoms, offering detailed visualisations and deep physical insight into the dynamics of the system. The book surveys studies of the energy shift of Rydberg atoms and molecules, the shapes of the spectral lines they emit, and counterintuitive phenomena observed in the process. At the cutting edge of its field, this research and reference text is ideal for graduate level students and researchers in quantum optics, quantum computing, plasma, and sensing technologies.